INTERNALISASI NILAI-NILAI PENDIDIKAN ISLAM DALAM MEMBANGUN KESADARAN EKOLOGIS SISWA DI GREEN SCHOOL SD IPK HIDAYAH TAYU - Nur Inayah; Nor Faizah; Salmah Fa’atin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to describe the process of internalizing Islamic educational values ​​in shaping students' ecological awareness at SD IPK Hidayah Tayu, a green school. This study used a descriptive qualitative approach, with the principal, Islamic Religious Education teachers, and students as subjects. Data were obtained through observation, interviews, and documentation, then analyzed using the Miles and Huberman model, which includes data reduction, data presentation, and conclusion drawing. The results indicate that value internalization occurs through three stages: value transformation, value transaction, and trans-internalization. Islamic values ​​such as trustworthiness, responsibility, and environmental stewardship are implemented through environmental awareness activities, Clean and Healthy Saturdays, plant care and fish farming projects, and water conservation. This process aligns with Hakam & Nurdin's theory of value internalization, Ki Hadjar Dewantara's value education, and Howard Gardner's theory of naturalistic intelligence. The results confirm that Islamic education plays a crucial role in fostering students' character that is faithful, responsible, and environmentally conscious.